Measuring religious values development based on Maqasid Syariah approach in compliance behavior of business Zakat Scenario / Mohd Rahim Khamis. - Khamis, Mod Rahim (Universiti Teknologi MARA Cawangan Selangor, 2016)
Religious values are one of the important aspects in explaining human behavior. However, lack of study focused on how to develop and measuring the religious values are hardly found in literature since the issue is important to discuss to produce good results. Hence, the main objective of this study is to develop the measurement instrument in measuring religious values based on Maqasid Al-Syariah approach as guideline in compliance behavior of business zakat scenario. 276 questionnaires managed to be collected from SMEs entrepreneurs in Selangor. Rasch Measurement Model was employed to analyze the data. From the results of item polarity and misfit indicates that all items measured religious values really measured what supposedly to measure since all items fit with the Rasch Measurement Model. The implication of this paper provides evidence of the usefulness of Maqasid Al-Syariah approach as a guideline in order to develop the measurement of religious values in compliance behavior of business zakat scenario. At the same, it also suggests that Rasch Measurement Model the usefulness of Rasch Measurement Model in analyzing the items that measured what supposedly to measure.